Heparanase is the possible link between monkeypox and Covid-19: robust candidature in the mystic and present perspective - Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; ‏Helal F. Hetta; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (AMB Express, 2023)
Abstract Heparanase (HPSE) is an endoglycosidase cleaves heparan sulfate (HS) and this contributes to the degradation and remodeling of the extracellular matrix. HS cleaved by HPSE induces activation of autophagy and formation of autophagosommes which facilitate binding of HPSE to the HS and subsequent release of growth factors. The interaction between HPSE and HS triggers releases of chemokines and cytokines which affect inflammatory response and cell signaling pathways with development of hyperinflammation, cytokine storm (CS) and coagulopathy. HPSE expression is induced by both SARS-CoV-2 and monkeypox virus (MPXV) leading to induction release of pro-inflammatory cytokines, endothelial dysfunction and thrombotic events. Co-infection of MPX with SARS-CoV-2 may occur as we facing many outbreaks of MPX cases during Covid-19 pandemic. Therefore, targeting of HPSE by specific inhibitors may reduce the risk of complications in both SARS-CoV-2 and MPXV infections. Taken together, HPSE could be a potential link between MPX with SARS-CoV-2 in Covid-19 era.